Analisis Korelasi Product Moment Dalam Menentukan Hubungan Kedisiplinan Mengajar Guru Pendidikan Agama Islam Dengan Kedisiplinan Belajar Siswa di Sekolah Menengah Pertama Negeri 2 Tandun - Efendi, Rahmi Maldini; Risnawati, Risnawati; Hamdani, M. Fikri (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the relationship between the teaching discipline of Islamic Religious Education teachers with student learning discipline at State Junior High School 2 Tandun. This research is a type of correlation research with a quantitative approach. The population in this study was 237 people and a sample of 20% with a total of 47 people. Sample withdrawal using proported stratified random sampling technique, which is stratified or tiered in a balanced manner. Data collection using lift, documentation, and observation. Data analysis technique using product moment correlation test. Based on the results of data analysis, it is known that there is a significant and positive relationship between the discipline of teaching Islamic Religious Education teachers with student learning discipline at State Junior High School 2 Tandun, obtained the value of r_hitung> r_tabel which is 0.552> 0.288, with a significant level smaller than α (5%) which is 0.000 <0.05. Keywords: Teaching Discipline, Learning Discipline, Islamic Religious Education.